Reading in The Digital Era : How Parentâ€™s Academic Background and Self-Efficacy Influence Childrenâ€™s Reading Habits - Ratnasari, Ana; Hernawan, Asep Herry; Dewi, Laksmi (Jurnal Kependidikan : Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran, dan Pembelajaran, 2025)
This study aims to analyze the relationship between parental educational background, self-efficacy, and children’s reading habits in the digital era. Using a correlational quantitative research method, the study involved 408 parents in West Jawa with children aged 4â€“8 years. The sampling technique used was multistage random sampling. Data were collected through an online Likert-scale questionnaire and analyzed using ordinal logistic regression. The findings indicate that parental self-efficacy significantly influences children’s reading habits (B = 0.247; p < 0.001), while parental educational background does not have a direct significant effect (p > 0.05). The model’s Nagelkerke RÂ² value of 0.494 suggests that 49.4% of the variance in children’s reading habits can be explained by parental self-efficacy and educational background. These results highlight the importance of parental confidence in supporting children’s literacy, which can be enhanced through family literacy intervention programs. Thus, this study contributes new insights into the psychological and environmental factors affecting children’s reading habits.